Analysis of Family Function and Family Type Towards Nutritional Status of Toddlers - Anggina, Dientyah Nur; Asmalia, Resy; Pramasyastri, Vina; Arifin, Stievy (Jurnal Kesehatan Manarang, 2025)
Nutritional status reflects the balance between nutrient intake and physiological needs, serving as a comprehensive indicator of an individual's nutritional condition. A well-functioning family influences maternal behavior in fulfilling children's nutritional needs, which can be affected by the number of family members living in the household. Assessing nutritional status is essential for supporting children's growth and development. This study aimed to identify the relationship between family function and family type with the nutritional status of toddlers in Seberang Ulu II Subdistrict. Anthropometric measurements were carried out on toddlers aged 12–60 months, and family-related data were collected using structured questionnaires. An observational analytic study with a cross-sectional approach was employed. A total sampling technique resulted in 75 participants. Data were analyzed using the Chi-square test and Fisher's exact test. The analysis revealed a significant relationship between family function and the nutritional status of toddlers (P=0.000). However, no significant relationship was found between family type and the nutritional status of toddlers (p=0.193). In conclusion, this study highlights a significant association between family function and toddler nutritional status in Seberang Ulu II Subdistrict, while family type showed no significant effect. These findings suggest that enhancing family functioning should be prioritized in efforts to improve toddler nutrition.